Di-tert-butyl N,N `-(octahydropentalene-2,5-diyl) dicarbamate - Kendhale, Amol M.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2008)
In the molecule of the title compound, C18H32N2O4, the central bicyclo[3.3.0] octane (octahydropentalene) has a rigid ring junction. Both rings of the bicyclo[3.3.0] octane unit adopt an envelope conformation, and the flexible tert-butylcarbamoyl side chains each have an extended conformation. Such a constrained bicyclo[3.3.0] octane aliphatic template is of interest with respect to the design of novel self-assembling motifs. Molecules related by c-glide symmetry are linked via intermolecular N-H center dot center dot center dot O hydrogen bonds, forming a two-dimensional layer structure. Neighboring layers are weakly associated along the a axis due to the close approach of the tert-butylcarbamoyl groups (2.55 angstrom).

Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Design and synthesis of bile acid-based amino sterols as antimicrobial agents - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Shukla, Praveen K.; Gonnade, Rajesh G. (Bioorganic & Medicinal Chemistry Letters, 2009)
New bile acid-based amino sterols were synthesized in good yields from C-3 beta-oxiranes as key intermediates. These derivatives were evaluated for their in vitro antimicrobial properties against human pathogens. These compounds showed better antibacterial activity as compared to antifungal activity. Compounds 21 and 22 showed comparable antibacterial activity to gentamicin against Staphylococcus aureus with IC(50) values of 5.14 and 4.46 mu g/mL. This is the first report for the synthesis of C-3 beta-oxiranes on the steroids having A/B cis ring junction and these oxiranes have been used for the synthesis of amino sterols 17, 18, 21, and 22. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amino sterols; Antibacterial agent; bile acid; Oxirane

Dipolar S=O center dot center dot center dot C=O and C-H center dot center dot center dot O interactions in the molecular organization of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
In the absence of conventional hydrogen bonding, the molecules of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoformate, C(18)H(20)O(10)S, (I), and 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthobenzoate, C(24)H(24)O(10)S, (II), are associated via C-H center dot center dot center dot O interactions. Molecules of (II) are additionally linked via dipolar S=O center dot center dot center dot C=O contacts. It is interesting to note that the sulfonyl O atom involved in the dipolar S=O center dot center dot center dot C=O contacts does not take part in any other interaction, indicating the competitive nature of this contact relative to the weak hydrogen-bonding interactions.

Design and development of POCN-pincer palladium catalysts for C-H bond arylation of azoles with aryl iodides - Khake, Shrikant M.; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2014)
{Well-defined and efficient POCN-ligated palladium complexes have been developed for the direct C H bond arylation of azoles with aryl iodides. The phosphinite-amine pincer ligands 1-(R2PO)-C6H4-3-((CH2NPr2)-Pr-i) 1R2POCNIPr2-H; R = `Pr (1a)

Diels-alder reaction of tropones with arynes: synthesis of functionalized benzobicyclo[3.2.2]nonatrienones - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Bisht, Rajesh H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
A new procedure for the mild, practical, and scalable Diels–Alder reaction of tropones with arynes is reported. Differently substituted tropones undergo selective [4 + 2] cycloaddition with arynes generated in situ by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates, allowing the formation of functionalized benzobicyclo[3.2.2]nonatrienone derivatives in moderate to good yields. In addition, the photophysical properties of the cycloadducts are presented.

Diastereoselective synthesis of cyclopentanone-fused spirooxindoles by N-heterocyclic carbene-catalyzed homoenolate annulation with isatilidenes - Patra, Atanu; Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Chemistry Frontiers, 2015)
N-Heterocyclic carbene (NHC)-catalyzed formal [3 + 2] annulation of α,β-unsaturated aldehydes with N-substituted isatilidenes resulting in the diastereoselective synthesis of cyclopentanone-fused spirooxindoles is demonstrated. Mechanistically, the reaction proceeds via the generation of homoenolate equivalent intermediates from NHC and enals, which on interception with isatilidenes afford spiroheterocyclic compounds bearing an all-carbon quaternary spiro-center in moderate to good yields and generally with high diastereoselectivity. Moreover, the functionalization of the spirooxindoles as well as the initial studies on the enantioselective version of this reaction are presented.

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Development of (quinolinyl)amido-based pincer palladium complexes: a robust and phosphine-free catalyst system for C–H arylation of benzothiazoles - Pandiri, Hanumanprasad; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2017)
(Quinolinyl)amido-ligated palladium(II) complexes have been synthesized and applied in the catalytic C–H bond arylation of benzothiazoles. The tridentate ligand precursors R2N-C(O)CH2-(NH)-C9H6N [(R2NNN8-Q)–H; R2N = morpholinyl, Me-N-piperazinyl] and the pincer palladium complexes [κN,κN,κN-{R2N-C(O)CH2-(μ-N)-C9H6N}]PdX [(R2NNN8-Q)PdX {R2N = Et2N, morpholinyl, Me-N-piperazinyl; X = OAc or Cl}] were efficiently synthesized, and characterized by various analytical techniques. The iodo derivative (Et2NNN8-Q)PdI was obtained in excellent yield by the treatment of the complex (Et2NNN8-Q)PdCl with KI. The molecular structures of complexes (Et2NNN8-Q)Pd(OAc) (2a), (Et2NNN8-Q)PdCl (3a) and (Et2NNN8-Q)PdI (4a) were elucidated by X-ray crystallography. Complex 3a was found to be the most efficient catalyst for direct C–H bond arylation of substituted benzothiazoles with diverse aryl iodides using a mild base, K2CO3. The working catalyst system 3a is highly robust and can be recycled and reused several times for the arylation of benzothiazole without loss of catalytic activity. Preliminary mechanistic investigations using controlled studies and kinetic analysis have been performed, which greatly support a molecular mechanism for the arylation.

Drug-drug cocrystals of anticancer drugs erlotinib-furosemide and gefitinib-mefenamic acid for alternative multi-drug treatment - George, Christy P.; Thorat, Shridhar H.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (Crystengcomm, 2020)
Drug-drug cocrystals of anticancer drugs erlotinib and gefitinib with furosemide and mefenamic acid, respectively, have been synthesized. The 1:1 erlotinib-furosemide cocrystal crystallizes in the monoclinic centrosymmetric P2(1)/n space group containing one molecule of each component in the asymmetric unit. In contrast the 1:1 gefitinib-mefenamic acid cocrystal hydrate belongs to the monoclinic centrosymmetric P2(1)/c space group comprising one molecule of both drugs along with one water molecule in the asymmetric unit. The solubility and dissolution rate study revealed higher solubility for BCS class II drugs, furosemide, and mefenamic acid, while the solubility and dissolution rate of erlotinib showed a significant reduction in the cocrystal salt. Conversely, the solubility of gefitinib didn't reveal a substantial decrease; however, the dissolution rate has been reduced in the cocrystal hydrate. Further, an attempt has been made to correlate the crystal structures of the erlotinib-furosemide and gefitinib-mefenamic acid cocrystals with their solubilities and dissolution rate.

Divergent approach to the synthesis of (-)-balanol heterocycle and cis-3-hydroxypipecolic acid based on chiral 2-aminoalkanol equivalent - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron, 2021)
Enantioselective synthesis of the hexahydroazepine core of (-)-balanol and formal synthesis of cis-3hydroxypipecolic acid from a common intermediate have been accomplished by a divergent path. The common intermediate was accessed from a favorably protected enantiomerically pure 2-amino-1,3,4-butanetriol (ABT) equivalent via oxidation and Wittig olefination. The synthesis of (-)-balanol heterocycle featured tandem reduction/acetal-deprotection/gamma-lactonization reaction and a one-pot azide reduction followed by seven membered aza-heterocycle formation while the route to cis-3-hydroxypipecolic acid highlighted the base induced piperidine ring formation and regioselective benzylidine-acetal cleavage. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Amino-alcohol; desymmetrization; Hexahydroazepine; Piperidine alkaloids; Protein kinase

Dynamic kinetic resolution of gamma,gamma-disubstituted indole 2-carboxaldehydes via NHC-Lewis acid cooperative catalysis for the synthesis of tetracyclic epsilon-lactones - Balanna, Kuruva; Barik, Soumen; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (2022)
The ubiquity of epsilon-lactones in various biologically active compounds inspired the development of efficient and enantioselective routes to these target compounds. Described herein is the enantioselective synthesis of indole-fused epsilon-lactones by the N-heterocyclic carbene (NHC)-Lewis acid cooperative catalyzed dynamic kinetic resolution (DKR) of in situ generated gamma,gamma-disubstituted indole 2-carboxaldehydes. The Bi(OTf)(3)-catalyzed Friedel-Crafts reaction of indole-2-carboxaldehyde with 2-hydroxy phenyl p-quinone methides generates gamma,gamma-disubstituted indole 2-carboxaldehydes, which in the presence of NHC and Bi(OTf)(3) afforded the desired tetracyclic epsilon-lactones in up to 93% yield and >99 : 1 er. Moreover, preliminary studies on the mechanism of this formal [4 + 3] annulation are also provided.

Desymmetrization of myo-inositol - Patil, Nivedita T.; Patil, Madhuri T.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Carbohydrate Research, 2025)
Chemistry and biology of phosphoinositols have been intensely investigated areas of research over the last 4-5 decades due to their involvement in cellular signal transduction pathways. Efficient laboratory synthesis of enantiomeric derivatives of inositols was a central issue since they were required for the delineation of the myo-inositol cycle as well as for the total synthesis of polyol based natural products and their derivatives. This essentially meant the development of competent methods for the desymmetrization of myo-inositol leading to the preparation of enantiomeric O-substituted derivatives of myo-inositol. This was approached by: the classical resolution methods involving separable diastereomers, the chiral pool synthesis, enzyme catalysis, asymmetric catalysis and preferential crystallization of enantiomers in a racemic conglomerate. This review summarizes results obtained in author's laboratory, as well as those reported in the literature on attempts at desymmetrization of myo-inositol.
Keywords: Conglomerate; Crystallization; Cyclitol; Enantiomers; Inositol; Lipid